Three Studies of Transitions of Young People in Public Care: A Focus on Educational Outcomes - Tessier, Nicholas (Université d'Ottawa / University of Ottawa, 2015)
The educational outcomes of children in care, as they prepare for and eventually complete the transition out of care, have been the subject of a growing body of research. Despite the progress made, no unified theory of risk and protective factors associated with educational outcomes has yet arisen from the longitudinal, cohort, and cross-sectional studies conducted with youth in care. This dissertation presents three papers that examine the effects of risk and protective factors on a range of educational outcome variables. The studies follow the timeline of a young person preparing for transition, moving into supported transitional living, and then eventually exiting care altogether. Study 1 presents cross-sectional and longitudinal tests of the generalizability of many of the risk and protective factors identified by O’Higgins, Sebba, & Gardner (2014) in their systematic review of predictors of educational achievement among young people living in foster or kinship care. The cross-sectional sample consisted of 3,662 young people aged 12 to 17 years who were residing in out-of-home care in Ontario, Canada. An additional longitudinal sample was composed of a subsample of 962 young people from the cross-sectional sample who had also been assessed 36 months later with the AAR-C2-2010 during year 13 (2013-2014) of the OnLAC project. Supporting evidence for twelve of the twenty factors identified by O’Higgins et al. are revealed in the broad cross-sectional study and for the four factors that were found to predict change in academic success over a longitudinal timeframe suggest we are on the right track. Study 2 uses a lag-as-moderator approach to see if the time between assessments influences the predictive capacity of variables assessed when the young person was in care to predict educational variables evaluated when the youth had completed the transition to support independent living. Results from this thorough methodological study of gap length over six years of OnLAC data are encouraging: 87.5% of the predictors tested for statistical moderation effects by the length of time between assessments were shown to be stable predictors across all gaps (i.e., no moderation by gap length effect). Study 3 presents a pilot 12-month follow-up study conducted with young people at the point of a major transition within or from child welfare services, comparing their characteristics with those of samples from the general population. When assembled together, the three studies provide a foundation towards the formalizing of a list of risk and protective predictors of educational outcomes (namely, academic success, educational attainment, educational aspirations, and NEET status) originally selected from a systematic review that identified a range of factors to be associated with the educational outcomes of youth in care (O’Higgins, Sebba, and Gardner; 2014). Additionally, this dissertation presents a series of recommendations regarding the management and multiple imputation of missing data and the use of Lag as Moderator statistical methods in child welfare research.
Keywords: Child welfare; Children; Youth; In-care; Foster care; Kinship care; Public care; Multiple imputation; Multiple regression; Lag as modetor